2013
DOI: 10.1186/1748-5908-8-95
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implement shared decision making in multidisciplinary sciatica care: a qualitative study

Abstract: BackgroundThe Dutch multidisciplinary sciatica guideline recommends that the team of professionals involved in sciatica care and the patient together decide on surgical or prolonged conservative treatment (shared decision making [SDM]). Despite this recommendation, SDM is not yet integrated in sciatica care. Existing literature concerning barriers and facilitators to SDM implementation mainly focuses on one discipline only, whereas multidisciplinary care may involve other barriers and facilitators, or make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 25 publications
9
51
2
1
Order By: Relevance
“…External factors outside of the physician's perceived control contributed to the low score in perceived behavioural control. This resonates with other research findings, in which physicians experienced many barriers owing to external factors when implementing SDM (Gravel et al, ; Hofstede et al, ). In a review study by Gravel et al (), the most important obstacles to implementing SDM mentioned by physicians were time constraints, characteristics of the patient and clinical context.…”
Section: Discussionsupporting
confidence: 89%
“…External factors outside of the physician's perceived control contributed to the low score in perceived behavioural control. This resonates with other research findings, in which physicians experienced many barriers owing to external factors when implementing SDM (Gravel et al, ; Hofstede et al, ). In a review study by Gravel et al (), the most important obstacles to implementing SDM mentioned by physicians were time constraints, characteristics of the patient and clinical context.…”
Section: Discussionsupporting
confidence: 89%
“…Each new transcript was systematically compared with prior ones, to ensure that characteristics of and differences between the data were identified and incorporated into the analysis. We used concept maps, with our research questions as a framework, to group the data and to look for similarities and differences across the data . The most important themes regarding SDM (mentioned in all focus groups) and their relationships are displayed in concept maps shown in Figure A,B (patient and professional perspectives, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare worker-related factors and information sharing and dialogue: initial tool (88 items) The six components identified from the models of Longtin et al (2010) and Tambuyzer et al (2011) were further developed with research from the literature review. Hofstede et al (2013) found that lack of knowledge about shared decision making, poor professional behavior and negative interpersonal relationships were perceived by patients and healthcare workers as barriers on micro-level for patient participation. These three elements (i.e.…”
Section: Demographic Variables and Care Settingmentioning
confidence: 99%